Advances in resistance breeding and integrated strategies for managing anthracnose in leguminous vegetables - Saranya, S; Sarada, S; Merin, E G; Joy, M; Beena, T; Swapna, A; Beena, R (Plant Science Today, 2025)
Anthracnose, caused by hemibiotrophic fungi of the Colletotrichum genus, is a major fungal disease of leguminous vegetables, leading to substantial yield losses and economic damage worldwide. Currently, cultural practices and substantial use of synthetic fungicides are the primary approaches for managing anthracnose. However, there is a growing focus on developing advanced breeding lines and cultivars with improved resistance to anthracnose. Traditional breeding has led to the identification of a wide range of anthracnose resistance resources, particularly in common bean, soybean, lentil, cowpea and lupins. Recent advances in molecular approaches, including genomics, transcriptomics, proteomics and metabolomics, have enhanced our understanding of the pathogenesis and defense mechanisms involved in the Colletotrichum-legume interaction. Genetic manipulation through omics technologies improves the efficiency of breeding programmes thereby offers better scope to protect legumes from anthracnose. This review focuses on key pathogens causing anthracnose in legumes, including C. truncatum, C. lentis, C. lupini, C. lindemuthianum and their biology and epidemiology. We discuss disease management strategies, including progress with host resistance, genetic and breeding approaches and highlight critical knowledge gaps in conventional and molecular breeding programmes. The continuous advancement in developing breeding lines, cultivars and donor plants with enhanced resistance to anthracnose in legumes driven by omics-based approaches is providing new understanding of legume-pathogen interactions. This progress supports the development of more sustainable and efficient strategies for managing the diseases in the future.